2010
DOI: 10.1111/j.1447-0756.2010.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Takayasu arteritis: A single centre experience from North India

Abstract: Adequate control of blood pressure during pregnancy, planning the timing and mode of the delivery and vigilant monitoring during intrapartum period with special reference to management of blood pressure and its complications is essential for an optimum outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 10 publications
4
58
3
Order By: Relevance
“…It is the presenting feature in TA and pregnancy, and pre-eclampsia complicated 62% of cases in a recent single-center Indian study [47]. Pregnancy complications and cesarean section were significantly higher in BD patients than in controls [45], as with most other vasculitides, particularly TA and WG.…”
Section: Effects Of the Rheumatological Disease And Pregnancy On The mentioning
confidence: 99%
“…It is the presenting feature in TA and pregnancy, and pre-eclampsia complicated 62% of cases in a recent single-center Indian study [47]. Pregnancy complications and cesarean section were significantly higher in BD patients than in controls [45], as with most other vasculitides, particularly TA and WG.…”
Section: Effects Of the Rheumatological Disease And Pregnancy On The mentioning
confidence: 99%
“…19 Maternal death by exacerbated hypertension and its complications. 18 Abruption, Cardiac failure, described in 2 studies. 20 The rare, potentially fatal maternal complications such as aortic aneurysm, cerebral haemorrhage, has also been reported.…”
Section: Criteria For Remissionmentioning
confidence: 99%
“…[16][17][18] Involvement of abdominal aorta and renal vessels could be the cause for higher incidence of IUGR (29.5%) and poor perinatal outcome. Pulmonary hypertension is a common feature with high maternal mortality.…”
Section: Criteria For Remissionmentioning
confidence: 99%
“…Earlier literature has suggested that most of the pregnant patient with TA reached successfully till term and had vaginal deliveries with fair fetal outcome. Those patients were mostly of types I and II TA [12,13]. Incidences of secondary HT and IUGR were low in those patients.…”
Section: Case Reportmentioning
confidence: 99%